2020
DOI: 10.1051/matecconf/202032107014
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Investigation of Titanium Hydride Formation from Reduction of Titanium (Ⅳ) Chloride with Magnesium Hydride in Presence of Hydrogen Atmosphere

Abstract: Thermodynamic assessment and experimental investigation for formation of titanium hydride (TiH2) from reduction of titanium tetrachloride (TiCl4) with magnesium hydride (MgH2) were carried out under hydrogen atmosphere. In this method, TiH2 production at low temperature was investigated, which can be used for further dehydrogenation process in titanium powder metallurgy. The effects of temperature, time, amount of titanium trifluoride (TiF3) as catalyst, and ball milling time of MgH2 on reduction process were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the current study, the TiH 2 was synthesized from TiCl 4 gas reacted with the MgH 2 powder at 500 • C for 12 h at the lab scale. Our previous attempts to synthesize TiH 2 at a temperature between 250 and 500 • C indicated that higher temperatures positively impacted the formation of TiH 2 [24][25][26][27][28]. The reduction products were then washed with water and diluted HCl to separate TiH 2 powder from the reaction byproducts.…”
Section: Synthesis Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the TiH 2 was synthesized from TiCl 4 gas reacted with the MgH 2 powder at 500 • C for 12 h at the lab scale. Our previous attempts to synthesize TiH 2 at a temperature between 250 and 500 • C indicated that higher temperatures positively impacted the formation of TiH 2 [24][25][26][27][28]. The reduction products were then washed with water and diluted HCl to separate TiH 2 powder from the reaction byproducts.…”
Section: Synthesis Processmentioning
confidence: 99%
“…The obtained TiO x C y N z is then chlorinated at 400 • C to produce TiCl 4 gas [22,23]. The author proposed directly reacting the obtained TiCl 4 gas with metal hydrides such as MgH 2 to produce TiH 2 powder at low-temperature ranges under the hydrogen (H 2 ) atmosphere [24][25][26]. The TiH 2 powder can then transform into Ti powder through the dehydrogenation process in a vacuum.…”
Section: Introductionmentioning
confidence: 99%